Identifying Racism and Racial Stereotypes in Rainbow Rowell’s Eleanor and Park - Sofyani, Rizki Amelia; Rangkuti, Rahmadsyah; Lubis, Masdiana (RADIANT: Journal of Applied, Social, and Education Studies, 2022)
The study aims to identify racism and racial stereotype in text structure, social cognition, and social context of Rainbow Rowell’s Eleanor and Park. The study uses qualitative descriptive design and conducts Teun A. van Dijk’s socio-cognitive approach to analyze words, phrases and sentences which contain racism and racial stereotype in Eleanor & Park. The result shows that racism in Eleanor and Park novel are in the form of implicit, explicit, internalized racism, and fetishism of Asian. The racial stereotypes in the novel are the stereotypes of Asian physical features, namely the description of a short body, slanted eyes, weak and helpless appearances, and also the use of the word "doll" to describe Asian women. The cause of racism and racial stereotypes in the novel are triggered by the inequality of access and power, lack of awareness about racial issues faced by Asian communities in western countries, and the development of the term "Model Minority" which makes an illusion that Asian community are privileged.